Implementasi Metode RAD dalam Pengembangan SIPERASUK di Bidang Perekonomian SETDA Kabupaten Malaka - Mirja Hoar; Yoseph Pius Kurniawan Kelen; Krisantus Jumarto Tey Seran (Saintek Lahan Kering, 2022)
A letter is a sort of communication between two people or more. Letters can come in two types, namely personal or public. Letters undeniably contain important information. There are various kinds of letters, such as invitations, personal and official letters and so on. In an institution, letters must be treated as important documents which play an important role in the institution, given letters are actually official written communication to be kept well. The Secretariat Department of Economy Malaka District has a huge number of letters. The letters in this department are conventionally typed in papers that makes letter filing complicated. Letters are piled in huge stacks that covers a lot of spaces in the office. On top of that, letters might easily get lost, misplaced those results in uneasiness to find and destroyed. In this research we introduced a computerized filing system to file the incoming and outgoing letters. In developing the system, we employed desktop usage using Rapid Application Development (RAD). The system is designed to manage the flow of in and out letters of the office. We hope that such a newly introduced computerized filing system can help ease the management of the filing of the flow of letters in the Secretariat Department of Economy, in Malaka District.